2022
DOI: 10.3390/agronomy12102321
|View full text |Cite
|
Sign up to set email alerts
|

Soil Biochar Application: Assessment of the Effects on Soil Water Properties, Plant Physiological Status, and Yield of Super-Intensive Olive Groves under Controlled Irrigation Conditions

Abstract: The effects of olive waste biochar and green compost as soil amendments on soil physical properties, as well as on physiological parameters and yield of a super-intensive olive crop cultivated under deficit irrigation conditions, were investigated in south-west Spain during the 2021 growing season. Thus, soils were amended with 40 t ha−1 of olive pomace waste biochar, green-compost, or a biochar-compost mixture (50% w/w), and no amended plots were used as control. On a bi-monthly basis, soil pH, water holding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Research has shown that increasing the organic matter content by means of composting also increases the water retention of the substrate [33]. Applying coconut bran and biochar to organic fertilizers can improve the soil's physicochemical properties and stimulate crop root growth and development [34][35][36]. Incorporating vermicompost and coconut bran increased the organic matter, alkaline dissolved nitrogen, quick-acting potassium and effective phosphorus contents of the substrate, which is similar to the findings by Bellitürk K et al [37].…”
Section: Comprehensive Evaluation Of Strawberries Based On Principal ...mentioning
confidence: 99%
“…Research has shown that increasing the organic matter content by means of composting also increases the water retention of the substrate [33]. Applying coconut bran and biochar to organic fertilizers can improve the soil's physicochemical properties and stimulate crop root growth and development [34][35][36]. Incorporating vermicompost and coconut bran increased the organic matter, alkaline dissolved nitrogen, quick-acting potassium and effective phosphorus contents of the substrate, which is similar to the findings by Bellitürk K et al [37].…”
Section: Comprehensive Evaluation Of Strawberries Based On Principal ...mentioning
confidence: 99%
“…After applying OP biochars, even more pronounced impacts in soil EC were recorded [38,42,51,55,67]. Hmid et al [67] reported that the OP biochar application with 15% in sandy soil increased the EC from 0.06 dS m −1 to 0.19 dS m −1 , making it unlikely that amended soils have a detrimental effect on microbial activity and crop growth [117].…”
Section: As Soil Amendments or Conditionersmentioning
confidence: 99%
“…Hormesis is regularly detected, meaning that high biochar rates can harm plants, while low rates can be stimulatory. Both positive [39,40,46,47,51,55,68,72,79,81] and negative [33,42,57,59,60,74] responses have been found in field trials to enhance yield crop as a result of biochar application to soils (Table 6).…”
Section: Plant Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using biochar for various purposes depends on the biochar properties, including morphology, physical properties, and physicochemical properties [ [21] , [22] , [23] ]. One of the primary uses of biochar is as a soil amendment; such applications must take into account biochar pH, cation exchange capacity, and porosity [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%